Pulmonary embolism in a young patient: a case report - Vázquez-Ramírez, Rodanim (2024)
Pulmonary embolism is one of the leading causes of precordial pain in the hospital setting. We present the case of a 31-year-old male patient who reported sudden precordial pain and dyspnea with minor exertion, a significant elevation of D-dimer and, as revealed by computed tomography angiography (CTA), the presence of a thrombus in the main, segmental and subsegmental pulmonary branches. He underwent an embolectomy, with subsequent recovery and good progress. Pulmonary embolism produces pathophysiological interference with gas exchange and circulation, and the cause of death in these patients is right ventricular failure due to acute pressure overload. The most frequent clinical manifestations and signs are dyspnea, palpitations, chest pain, syncope and hemoptysis, tachycardia, tachypnea and jugular venous distension. The McGinn-White pattern consists of an electrocardiographic trace showing a deep S1 in lead DI, along with a Q wave and an inverted T wave in lead DIII. This electrocardiographic pattern has been reported in 7 % to 19 % of patients presenting with pulmonary embolism. Catheter-directed therapy is the treatment of choice in patients with intermediate risk and proximal thrombus in the pulmonary arteries. This approach includes catheter-directed thrombolysis and mechanical aspiration thrombectomy, yielding favorable results in reducing pulmonary hypertension and improving hemodynamic stability. However, these cases are rare in young people without major risk factors. Prompt management avoids associated complications such as right heart failure and prevents chronic complications.